2007
DOI: 10.1373/clinchem.2006.080051
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Diagnosis of Specific Antibody Deficiency to Pneumococcal Capsular Polysaccharide Antigens

Abstract: Background: Measurement of postimmunization antibody response to pneumococcal capsular polysaccharide (caps-PS) is the standard method to identify deficiency of antipolysaccharide antibody production. However, no standardized criteria have been defined for classification of patients into responders or nonresponders to caps-PS. Methods: We vaccinated 37 healthy children and 39 healthy adults with Pneumovax ® and measured the anti-caps-PS antibody response to 5 serotypes. We also measured antipneumococcal antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 27 publications
4
27
0
2
Order By: Relevance
“…Serotype 3 is known to be highly immunogenic and even immunogenic at earlier age (from 3 mo of age) (35,36, and own unpublished data). We also previously found that an inadequate response to serotype 3 predicts unresponsiveness to other serotypes (20). This finding has also been reported by Sorensen et al (37), who found that patients who failed to respond to serotype 3 at any age also failed to develop protective concentrations of Abs against the other serotypes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Serotype 3 is known to be highly immunogenic and even immunogenic at earlier age (from 3 mo of age) (35,36, and own unpublished data). We also previously found that an inadequate response to serotype 3 predicts unresponsiveness to other serotypes (20). This finding has also been reported by Sorensen et al (37), who found that patients who failed to respond to serotype 3 at any age also failed to develop protective concentrations of Abs against the other serotypes.…”
Section: Discussionsupporting
confidence: 89%
“…IgM and IgG Abs to cap-PS serotypes (20) and PspA were measured by ELISA, as previously described, but using a goat anti-human conjugate (21).…”
Section: Determination Of Abs To Caps-ps Serotype 3 and Pspamentioning
confidence: 99%
“…Antibodies to cap-PS serotypes were measured by an ELISA, as previously described (17,18). Sera were preabsorbed with C polysaccharide and serotype 22F to remove cross-reactive antibodies before application onto coated plates.…”
Section: Subjectsmentioning
confidence: 99%
“…For these studies, data from the laboratory clinical immunological investigation were used. This included data on antibodies to serotype 3 (strong immunogen), serotype 4 (intermediate immunogen), and serotype 9N (low immunogen) (18). The results are shown in Fig.…”
Section: Cd5mentioning
confidence: 99%
“…The range of normal baseline antibody levels against S. pneumoniae serotypes in healthy adults has been documented, [13][14][15] but what constitutes a protective level of antibody against each serotype and whether that protective titer is different for each serotype remains controversial. 16 Additionally, there is no universal definition of adequate response to pneumococcal vaccination for diagnosis of SAD despite meta-analysis and specificity studies. 17,18 Previous studies have described the range of postvaccination antibody levels in healthy individuals, revealing achievement of normal antibody titers (defined by antibody titer of >1.0 μg/mL or twofold increase in titer) against most serotypes in adults, 19,20 as well as a normal response (defined by serotype-specific antibody levels using alternate multiplexed bead assay) in >90% of normal patients.…”
Section: Discussionmentioning
confidence: 99%